Immunomodulatory Effects of Anadenanthera colubrina Bark Extract in Experimental Autoimmune Encephalomyelitis - Karla A. Ramos; Igor G. M. Soares; Larissa M. A. Oliveira; Mariana A. Braga; Pietra P. C. Soares; Gracimerio J. Guarneire; Elaine C. Scherrer; Fernando S. Silva; Nerilson M. Lima; Felipe A. La Porta; Teresinha de Jesus A. S. Andrade; Gagan Preet; et al. (Current Issues in Molecular Biology, 2024)
This study aimed to evaluate the efficacy of the ethanolic extract of Anadenanthera colubrina in modulating the immune response in the Experimental Autoimmune Encephalomyelitis (EAE) model. The ethanolic extract of the dried bark was analyzed by ESI (+) Orbitrap-MS to obtain a metabolite profile, demonstrating a wide variety of polyphenols, such as flavonoids and phenolic acids. Various parameters were evaluated, such as clinical signs, cytokines, cellular profile, and histopathology in the central nervous system (CNS). The ethanolic extract of A. colubrina demonstrated significant positive effects attenuating the clinical signs and pathological processes associated with EAE. The beneficial effects of the extract treatment were evidenced by reduced levels of pro-inflammatory cytokines, such as IL1β, IL-6, IL-12, TNF, IFN-γ, and a notable decrease in several cell profiles, including CD8+, CD4+, CD4+IFN-γ, CD4+IL-17+, CD11c+MHC-II+, CD11+CD80+, and CD11+CD86+ in the CNS. In addition, histological analysis revealed fewer inflammatory infiltrates and demyelination sites in the spinal cord of mice treated with the extract compared to the control model group. These results showed, for the first time, that the ethanolic extract of A. colubrina exerts a modulatory effect on inflammatory processes, improving clinical signs in EAE, in the acute phase of the disease, which could be further explored as a possible therapeutic alternative.